2002
DOI: 10.1051/0004-6361:20020804
|View full text |Cite
|
Sign up to set email alerts
|

X-ray emission from wind blown interstellar bubbles

Abstract: Abstract.We have observed the stellar wind blown bubble NGC 6888 with the ROSAT HRI. A map and a catalogue of X-ray filaments is derived, the typical filament being a few 0.1 pc in extent with an HRI count rate of a few 10 −4 s −1 . We show that this filamentary structure can qualitatively be modelled as local count rate enhancements due to denser gas near evaporating cool clumps which in turn are seen in the optical and probably are produced by instabilities after the passage of the primary shock front of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 17 publications
6
45
1
Order By: Relevance
“…There is only one more object, S308, that has been detected and studied in some detail. Analysis of the ROSAT (Wrigge et al 1994) and the XMMNewton (Chu et al 2003) observations of S308 showed that its X-ray spectrum is soft with plasma temperature of kT = 0.15 keV. Recent analysis of new XMM-Newton observations that completed coverage of this WBB observed in X-rays to 90% of its spatial extent confirmed the basic properties of the hot plasma in S308 (Toala et al 2012).…”
Section: Introductionmentioning
confidence: 87%
“…There is only one more object, S308, that has been detected and studied in some detail. Analysis of the ROSAT (Wrigge et al 1994) and the XMMNewton (Chu et al 2003) observations of S308 showed that its X-ray spectrum is soft with plasma temperature of kT = 0.15 keV. Recent analysis of new XMM-Newton observations that completed coverage of this WBB observed in X-rays to 90% of its spatial extent confirmed the basic properties of the hot plasma in S308 (Toala et al 2012).…”
Section: Introductionmentioning
confidence: 87%
“…NGC 6888 was the first WBB that has been detected in X-rays, it was made with Einstein by Bochkarev (1988). The Wrigge et al (1994) X-ray observation did not detect a filled bubble emitting as models predicted, but a filamentary X-ray structure was instead found following the Hα features of the nebula. In addition, spectra in the shell were fit to a double-temperature plasma model with a high-temperature component at T ∼ 8.5 × 10 6 K and a low-temperature component at T ∼ 1.3 × 10 6 K without detecting significant temperature variation between different areas of the nebula (Wrigge et al 2005).…”
Section: Introductionmentioning
confidence: 94%
“…NGC 6888 around WR 136 (WN6) is often regarded as the archetypal WR bubble. It was first detected in the X-ray domain by the EINSTEIN satellite, but was more thoroughly studied using ROSAT data (Wrigge et al 1994, and references therein). The X-ray emission from NGC 6888 appears to be limb-brightened and is concentrated to the northeast and southwest parts of the nebula, where Hα appears the strongest.…”
Section: The Surrounding Nebula Rcw 58mentioning
confidence: 99%